A critical review of the symmetric punching shear of reinforced concrete flat slabs. - Grira, Mongi. (University of Ottawa (Canada), 1990)
An experimental investigation on model slabs and on a 1/3 scale composite bridge deck showed that the ultimate punching shear load depends on the shape of the loaded area, the compressive strength of concrete, the flexural reinforcement ratio and on the arrangement of steel bars. Punching failure follows the formation of an inclined failure surface from the edge of the loaded area to the opposite slab face running through the effective depth at a mean angle of 22 to 30 degrees. A study of the application of the yield line theory proves that flexure theory alone is not recommended to treat local failure because of the violent and nonductile nature of punching shear failure. An explanation of the application of the strut and tie model to symmetric punching shear is given to provide a base for future experimental programs and the development of this approach. The mechanism of symmetric punching of slabs without shear reinforcement is described based on observations from tests. An empirical equation to determine the ultimate punching load of flat slabs is proposed. It is concluded that the proposed equation can predict the ultimate punching shear loads of flat slabs with confidence similar to Kinnunen and Nylander's model. Present North American codes should be updated to express the state of present day knowledge, particularly with the inclusion of the influence of the flexural reinforcement. (Abstract shortened by UMI.)
Keywords: Engineering, Civil.